Relationship between anxiety and internet searches before percutaneous ultrasound-guided diagnostic procedures: A prospective cohort study. - Marcio Meira; Almir Galvão Vieira Bitencourt; Demian Jungklaus Travesso; Rubens Chojniak; Paula Nicole Vieira Pinto Barbosa (PLoS ONE, 2022)
Invasive procedures guided by ultrasound (US) are part of routine medical diagnostic investigation. The lack of knowledge surrounding the technical aspects of such procedures can lead patients to seek complementary information on the Internet, which may in turn trigger anxiety. However, the intersection between the fields of Radiology and Psychology is poorly studied. Here, we identify the profile of an anxious patient before an US-guided intervention. We prospectively studied 133 patients undergoing image-guided procedures. The State-Trait Anxiety Inventory (STAI) was applied for psychometry. Significantly higher anxiety scores were observed in female patients (p = .001), those who believed they had received inadequate information from their referring physician (p = .006), and in patients who considered online information unreliable or difficult to access (p = .007 and p = .001, respectively). Participants who defined themselves as proactive online reported lower anxiety levels (p = .003).